Peran Unsur Meta-Utaut, Penerimaan Paylater dan Persepsi Penggunaan Terhadap Antropomofisme Indonesia - NadaFajar Nurmani'ah Widiarti; Nurkholis Nurkholis; Lilik Purwanti (Universitas Muhammadiyah Malang, 2024)
Purpose: Applying the integration of UTAUT and MTAM theories, this study investigates the acceptance and usage of paylater from the Indonesian anthropomorphism perspective. Methodology/approach: Quantitative research strategy using methods for gathering data via questionnaires. Using the Lameshow formula, which yields 384.16, the sample size was calculated and rounded to 400 individuals. The combined strategy of the SEM-ANN method is used in this study's data analysis. Findings: The research presented here demonstrates that behavioral intentions are mostly determined by their performance expectations. The elements of effort expectancy, social influence, facilitating condition, hedonic motivation, habit, and trust in shaping user behavioral intentions all support this. However, perceived risk and perceived cost have the effect of decreasing behavioral intention to use. One of the things that encourages usage behavior is its goal. Practical implications: This empirical study breaks out the paylater adoption-influencing aspects from an Indonesian social perspective. IT developers can create user-friendly or widely approved paylater applications in this approach. Originality/value: This study builds pricing value components by combining the UTAUT and MTAM methodologies with structural equation modeling (SEM) and analysis of neural network (ANN) techniques. In recognizing connections that are linear and non-linear.